Virtual Environments for the Treatment of Claustrophobia - Botella, C.; Quero, S.; Perpiñá, C.; Baños, R.M.; Alcañiz, M.; Lozano, J. A.; Rey, A. (International Journal of Virtual Reality, 1998)
Virtual Reality (VR) is a new technology that is having a great impact on various areas of health science. The use of VR is of special interest in the treatment of psychological disorders. Reasonable data exist on the effectiveness of this technology in the treatment of different anxiety disorders. The present paper explains in detail a psychological program for the treatment of claustrophobia using VR, whose effectiveness has already been demonstrated. (Botella et al.,1998). In addition, we describe the technical aspects of the software and point out several limitations VR still presents in the area of psychological treatment. Color images and video clips are included with the CDROM version.